Insights from national survey on household expenditure for primary healthcare services availed through informal healthcare providers - Banuru Muralidhara Prasad; Jaya Prasad Tripathy; Pruthu Thekkur; V R Muraleedharan (Journal of Family Medicine and Primary Care, 2021)
Introduction: Ensuring accessible and affordable primary healthcare services of optimal quality is a core component of universal health coverage (UHC). Though a substantial percentage of population avail healthcare services from informal healthcare providers (IHPs) in rural India, the information regarding the extent of out-of-pocket (OOP) expenditure during such encounters is limited. Method: The study analyzed publicly available data of 75th National Sample Survey (NSS) to understand the household expenditure pattern on availing service from IHPs. OOP expenditure for services availed from IHPs were extracted from main data sets and analyzed for both out-patient care and hospitalization. The OOP was summarized across the five wealth quintiles based on monthly per capita expenditure (MPCE) and disease groupings derived from the ailments recorded during the survey. Results: In total, 721 households accessed IHPs as part of out-patient consultation for infectious disease (67%). Households from rural areas (78%), households belonging to backward groups (75%), households from the poorest quintile and women (52%) access the services of IHPs. The median OOP for all services was INR 240 (IQR 120–600) and more than 90% of total OOP is accounted for medical expenditure. Conclusion: The programs need to define healthcare packages to engage IHPs to increase the reach and reduce OOP expenditure on households.